MUSYAWARAH PROVINSI POBSI KALIMANTAN SELATAN - H. Noor Fathulliansyah1 (Balanting, 2022)
AbstractImplementation is an activity that has been prepared in accordance with the program andobjectives, with the implementation of the Musprov it is expected to find a qualified generalchairman and sports administrator so that in the future it will give birth to professional athletesand become a means for athletes in the South Kalimantan region in developing talent towards aprofessional direction.Keywords: implementation, culture, economy